Colocalization of microtubules and mitochondria in the yeast Schizosaccharomyces japonicus var. versatilis - Svoboda, A; Slaninová, I (Canadian journal of microbiology, 1997)
Both living and fixed cells of Schizosaccharomyces japonicus var. versatilis showed thread-like mitochondria when studied by phase-contrast and fluorescence microscopy. In the interphase cells, mitochondria extended from pole to pole and converged towards the growing tips. The mitochondrial threads did not disrupt but persisted during mitosis and, subsequently, their bundle was split between the two daughter cells by a concentrically growing septum. Mitochondria in the interphase cells were accompanied by cytoplasmic microtubules. These disappeared during mitosis and, instead, spindle microtubules were formed in the nucleus. The cytoplasmic microtubules reappeared after anaphase B, again in coaligment with mitochondria. Protoplasting as well as the action of microtubule inhibitors methyl-1-(butylcarbamoyl)-2-benzimidazolecarbamate (benomyl) and 2-methylbenzimidazole (MBC) resulted in rapid disintegration of microtubules and, suprisingly, also in disruption of mitochondria into small bodies. Removal of the inhibitors or a short regeneration of protoplasts allowed both the cytoplasmic microtubules and the thread-like mitochondria to reaggregate into the original pattern. Cytochalasin D treatment caused a complete disintegration of actin filaments, while the cytoplasmic microtubules and mitochondria remained intact. These findings of a transient close association of mitochondria and microtubules and their relative independence of the arrangement of actin filaments suggest that microtubules, but not actin cables, form supports for positioning or movement of mitochondria along the cylindrical cells. The persistence of mitochondria in the cell centre during mitosis may be accounted for by the fact that disrupted microtubules fail to provide support for mitochondrial movement towards the cell poles.
Keywords: Benzimidazoles; Cell Cycle; mikrotubuly; Mitochondria; Cell Compartmentation; Cytochalasin D; Benomyl; Cytoplasm; Schizosaccharomyces; cytochalasin D; mitochondrie; benomyl; kompartmentace buňky; benzimidazoly; cytoplazma; buněčný cyklus; Microtubules